Sustainability in the Consumption of Luxury Products: An Analysis of Social implications - Roibu, Stefania-Cristina (Journal of Economic Development, Environment and People, 2023)
This study aims to demonstrate whether consumers seek to raise their social status by purchasing products sold at a high price. Also, the reason why customers of luxury companies prefer to buy them despite competitors with a lower price on the market. The purchase of premium products is influenced by the desire to change social status by expressing one’s personality and the need for inclusion in various interest groups. Awareness of the fundamental reasons on which decisions are made to purchase goods can be used both for marketing strategies and as a strategy for the long-term economic and social sustainability of a company on the market.